THE INFLUENCE OF GOOD CORPORATE GOVERNANCE AND FINANCIAL PERFORMANCE ON COMPANY VALUE IN INFRASTRUCTURE SECTOR COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE (YEAR 2015-2022) - Kusumawati, Indah; Mukhzarudfa, Mukhzarudfa; Hernando, Riski (Journal of Management Small and Medium Enterprises (SMEs), 2025)
This study aims to investigate the extent to which financial performance and Good Corporate Governance influence the valuation of infrastructure-sector firms listed on the Indonesia Stock Exchange over the 2015–2022 period. The independent variables of excellent corporate governance in this study are an audit committee, managerial ownership, institutional ownership, and an independent board of commissioners. The debt-to-asset ratio, current ratio, and return on assets make up the independent variables of financial success. Company value is the dependent variable, and Tobin's Q serves as a stand-in for it. The data analysis methodology used in this study was multiple linear regression analysis, which was performed with the SPSS software version 20. The findings showed that concurrent effects on the company value were caused by the audit committee, management ownership, institutional ownership, independent board of commissioners, return on assets, debt-to-asset ratio, and current ratio. Keywords: Good Corporate Governance; Financial Performance; Company Value